Prospects for optimizing the provision of medicines to pediatric patients based on the development of the pharmaceutical market in the segment of medicines for children - O. D. Nemyatykh; E. A. Kovaleva; I. A. Narkevich (Разработка и регистрация лекарственных средств, 2024)
Introduction. The strategy of drug supply to the population of the Russian Federation for the period up to 2025 highlights the need to ensure the rational use, safety and quality of medicines in the range of priority tasks. At the same time, the use of effective medical technologies in pediatric patients is limited both by the range of medicines approved for use in the pediatric population and by the requirements regarding compliance of the pharmaceutical design of the drug with the intended purpose in the target age group. The Russian pharmaceutical market is characterized by a monotonous and persistent tendency to expand the assortment matrix and increase the indicators of real and potential capacity, including in the segment of medicines for pediatrics. However, despite the introduction of new market positions for children into civil circulation, the gradual accumulation of data on the safety, clinical and clinical-economic effectiveness of drugs in the pediatric population, the expansion of the panel of possibilities of production pharmacies, the change in the legal status of registered drugs prescribed by off-label, based on evidence-based experience of use for a new purpose, the issues of the validity of medical prescriptions with an acceptable profile of convincing evidence in relation to pediatric patients in the context of the occurrence and development of a number of pathologies remain open.Aim. The aim of the work was to determine the prospects for optimizing the provision of medicines to pediatric patients based on the development of the pharmaceutical market in the segment of medicines for children.Materials and methods. The information base of the study was made up of data from the Ministry of Health of the Russian Federation for 2010–2022, GRLS as of 01.01.2023, as well as instructions for the medical use of medicines. The target age group of patients was determined in accordance with the Recommendation of the Board of the Eurasian Economic Commission. The content analysis method is used to search scientific literature in the PubMed and eLibrary electronic databases, analyze information from instructions for the medical use of medicines (LP), restrictive lists, GRLS, and the state register of prices for VED. The analysis of morbidity data was carried out using the statistical analysis method. Grouping, ranking and systematization were used in the framework of a structural analysis of morbidity, as well as an analysis of the assortment matrix of drugs for pediatrics within the established market boundaries. Graphical analysis was used to visualize the data. Data processing was carried out using MS Excel 2021.Results and discussion. It was found that in the period from 2010 to 2022, against the background of an increase in the number of children by 11.22 %, there was an increase in primary morbidity by 13.41 % in general. Respiratory diseases prevail in the structure of primary morbidity of children, amounting to 62.61 %. Having analyzed the matrices of the national pediatric code formulary, covering 554 INNs, it turned out that within the pharmacotherapeutic groups J, L, N and P themselves, a decrease in WHO indicators of 16–57 % was recorded. An assessment of the supply on the national market allows us to conclude that 19.55 % of drugs approved for use in pediatric practice are contraindicated in patients under 12 years of age. As a result of the assortment ranking along the route of administration, the predominance of oral forms was established, covering 39.88 % of the assortment matrix.Conclusion. Assessing the dynamics of morbidity in the context of analyzing the structure of the market of drugs for pediatrics allows us to identify priority niches for the pharmaceutical industry in the segments of medicines for the pharmacological correction of respiratory diseases, as well as drugs for the treatment of oncological pathologies, autoimmune disorders, obesity, diabetes mellitus and neurological disorders. The range of medicines presented today, taking into account the forms of release and age restrictions for the treatment of pediatric patients, demonstrates insufficient filling of the market with drugs in special children's dosage forms that ensure acceptability to modern concepts of therapy in pediatrics and accurate dosing of active substances in accordance with the age of the child, which, in turn, reveals the prospects for the pharmaceutical development of medicines with a design that corresponds to the purpose in the target age group.